Enhanced Friction and Wear Properties of TiN/MoS2 Composite Coating on the Surface of Plasma Nitrided Ti6Al4V Alloy - Hongyu Li; Kai Le; Ganggang Wang; Zhenghao Ren; Yuzhen Liu; Zhenglong Yang; Liwei Zheng; Shusheng Xu (Lubricants)
In this study, plasma nitriding and multi-arc ion plating techniques were employed to enhance the load-bearing capacity of the TC4 alloy. The tribological properties were characterized, and the mechanisms were discussed in detail. Subsequently, the tribological properties of the coating enhanced with MoS2 were then evaluated, and the results indicated that the plasma nitriding treatment, which exhibited optimal friction performance, resulted in the formation of a nitrided layer with a thickness of 98 μm on the surface of the TC4 alloy, thereby significantly improving its mechanical properties. Furthermore, the TiN coating samples treated with plasma nitriding demonstrated superior mechanical properties, achieving the highest hardness value (20 GPa), high load-carrying capacity (58 N) and the lowest wear rate (9.16 × 10−6 mm3·N−1·m−1). Moreover, the tribological properties of MoS2 deposited on the surface of the PN-2/TiN sample were significantly enhanced, which can be attributed to the synergistic effect of the excellent load-bearing characteristics of the plasma nitriding treatment and the wear resistance of the TiN layer. This study investigates the factors contributing to the superior tribological performance of the PN-2/TiN sample and the extended friction lifetime of the PN-2/TiN/MoS2 sample. The composite coating provides a new method to improve the anti-friction of soft metals, especially titanium alloys, and is expected to be applied in the aerospace field.